PERSEPSI ULAMA TENTANG TAYANGAN MISTIS â€œ(MASIH) DUNIA LAINâ€ DI STASIUN TELEVISI TRANS7 - Siswanta, Agus Sofyan, Dian Esti Nurati & (Transformasi, 2016)
This research aims to figure out the Ulama perception at Assalaam Islamic ModernsBoarding School (PPMI Assalaam) on Trans7â€Ÿs mystical program â€œ(Masih) DuniaLainâ€. The research uses descriptive qualitative method. The data are taken throughobservation, documentation and in-depth interview. An interactive analysis model fromMiles, Huberman and Saldana is used to analyze the data. The result shows that theUlama perceive that mystical television program i.e â€œ(Masih) Dunia Lainâ€ is a lowquality television program. They view that this program can destroy the Islamic creed(aqidah) of Muslim society.Key words: Perception Ulama, mystical program, television